Student Teachers’ Perceptions and Experiences on Mentoring Practices and Competence Development at Makerere University in Uganda - Bwiruka, Jane; Maani, John; Ssetumba, John (American Journal of Education and Practice, 2021)
Purpose: This study explored the perceptions and experiences of student teachers on mentoring practices and competence development at Makerere University in Uganda. Methodology: Basing on the three mentoring models of mentoring developed by Twoli (2011) as the analytical lens, this study explored the mentoring practices currently existing at Makerere University, the model of mentoring the University is aligned to and how it develops Student teachers' competences. The three mentoring models are the corporate model (traditional model), the more improved collaborative model and the emerging model of mentoring practices. Phenomenology was adopted as a qualitative research design anchored in the constructivist interpretivist paradigm. Data was collected using unstructured interviews from purposively selected twelve finalist student teachers and triangulated with review of documents and literature to cross validate the findings. Data was analyzed using the framework analysis. Findings: Makerere University is still tagged in the corporate/ traditional model of mentoring student teachers basing on the way they organize, supervise and moderate their student teachers on practicum. Unique Contribution to Theory, Practice and Policy: The Ministry of Education and Sports (MOE&S) in Uganda through the National Council for Higher Education (NCHE) should include mentorship programmes as a formalized minimum standard in teacher education institutions. Universities and other teacher preparation institutions should introduce mentorship programmes for university staff and schools. The study also recommended that lecturers and senior teachers should be sensitized about the effects of relying on the traditional/corporate mentoring model through professional development courses.